Passive cooling system for a sustainable future in hot-humid climate - Hj Mohd Ariffin, Noor Aziah; Sanusi, Aliyah Nur Zafirah; Mohd Noor, Aminuddin (2015)
One of the passive cooling strategies is the earth-air pipe heat exchanger (EAPHE). It is the cooling of outdoor air through underground pipes, using the soil as a heat sink to cool the passing air into the building. The EAPHE systems worked well in hot and dry climates. However, in the hot humid climate this passive cooling technology is relatively new. This paper reports on the process of selecting the most appropriate pipe materials for the EAPHE system for the hot-humid climate of Malaysia for a sustainable future. The study utilizing the EnergyPlus simulation program investigates the optimum pipe material through an exhaustive enumeration process. The study found that the polyethylene (PE) pipe material indicated the best performance.